NILAI-NILAI PENDIDIKAN AGAMA HINDU DALAM TRADISI NEDEH DI DESA KEKERAN KECAMATAN MENGWI KABUPATEN BADUNG: Hindu Religious Education Values NEDEH TRADITION IN KEKERAN VILLAGE Mengwi District BADUNG REGENCY - Putu Ayu Wulan Sri Diantari; Kadek Anggi Dwi Yanti,; I Nyoman Kiriana (Jurnal Pendidikan Agama, 2022)
Religious life in the practice of religious teachings is shaped by the cultural characteristics of each region. Religious teachings occupy a very important place in their lives and motivate the formation of a spirit of spiritual harmony in order to achieve the goals of Hinduism itself. The Nedeh ceremony is a series of religious activities where rice planting is carried out once every 50 days. Performing this ritual is a tribute to Dewi Sri for physical and mental well-being. The values ​​of Hindu religious education discussed in this study are: divine values, social values, aesthetic values, ethical or moral values ​​and the value of increasing morality and awareness, parallel. The existence of religious customs is supported by customs and religious customs. Pedagogical values ​​can shape and instill noble attitudes, personalities, and personalities so that humans can carry out their work in the future.